Associations of brain-natriuretic peptide, high-sensitive troponin T, and high-sensitive C-reactive protein with outcomes in severe aortic stenosis. - Andreas Auensen; Amjad Iqbal Hussain; Ragnhild Sørum Falk; Marte Meyer Walle-Hansen; Jorun Bye; Kjell Ingar Pettersen; Pål Aukrust; Thor Ueland; Lars Lysgaard Gullestad (PLoS ONE, 2017)
Among patients with severe aortic stenosis (AS), we investigated the associations of N-terminal pro-natriuretic peptide (NT-proBNP), high-sensitive troponin T (hsTnT), and high-sensitive C-reactive protein (hs-CRP) with 3-year mortality and major adverse cardiovascular events (MACE) during 1 year.This observational cohort study prospectively enrolled 442 patients with severe AS who were referred for evaluation of possible valve replacement. Clinical data was recorded before the decision of whether to operate was made. We studied the prognostic value of assessing biomarkers by serum levels, and tested associations of NT-proBNP, hsTnT, and hs-CRP with clinical outcomes (3-year all-cause mortality and risk of MACE in the year following study inclusion) using adjusted multivariable analysis.Elevated serum levels of these biomarkers at baseline evaluation were associated with increased all-cause 3-year mortality regardless of treatment assignment. Adjusted analysis showed that none of the studied biomarkers (NT-proBNP, hsTnT or hs-CRP) or any other covariates were associated with 3-year all-cause mortality following surgical aortic valve replacement (SAVR). However, adjusted analyses showed that hsTnT (HR, 1.51; 95% CI, 1.11-2.05; P = 0.008) and left ventricular ejection fraction (HR 0.97; 95% CI 0.94-0.97, P = 0.043) was associated with MACE for operated patients.Whereas NT-proBNP, hsTnT and hs-CRP had no independently prognostic value in relation to all-cause mortality following SAVR, hsTnT was independently associated with MACE following operation. The use of these clinically available biomarkers, in particular hsTnT, should be clarified in larger studies.